PENGEMBANGAN HANDOUT BERBASIS KONTEKSTUAL PADA PELAJARAN BIOLOGI MATERI BIOTEKNOLOGI UNTUK SISWA KELAS XII SMK NEGERI 02 BATU - Rahmayani, Fega; Hindun, Iin; Miftachul Hudha, Atok (Jurnal Pendidikan Biologi Indonesia, 2015)
PENGEMBANGAN HANDOUT BERBASIS KONTEKSTUAL PADA PELAJARAN BIOLOGI MATERI BIOTEKNOLOGI UNTUK SISWA KELAS XII SMK NEGERI 02 BATU Â  Fega Rahmayani1, Iin Hindun1, Atok Miftachul Hudha1 1Pendidikan Biologi FKIP Universtias Muhammadiyah Malang, e-mail : atok_emha@yahoo.com Â  ABSTRACT The teaching learning activity in SMK is inappropriate with the purpose of teaching and learning in SMK, which the students are taught to be able to apply the materials in the real life. Teaching material is taken from the biology book of SMA that the content is theoretically, so the explanation on the material is unsuitable and not applicative that makes the student less in ability and skill for application in daily life. From the problem above, this research purpose on developing the contextual basic handout of the biological course in biotechnology material in SMK N 02 Batu.This research is developing research based on research and development by Sugiyonoâs model that use a few developing steps, those are: (1) Potential and problem, (2) Collecting data, (3) Product design, (4) Validation design, (5) Design revision, (6) Try out the product, (7) Product revision. The data collecting methods is using validation from the expert of handout, material expert and try out to the study club. The technique of analyze data using quantitative and qualitative data. The result of quantitative data is the percentage of handout product value that classify in the handout quality and the result of qualitative data come from comment and advise of validator and try out in SMK.The result quality of the handout found that the developing contextual basic handout reach out the good quality after following the procedure of validation with percentage 80.90% and try out to the student that use the handout with percentage very good, 97.75% and get the positive respond from student with percentage 90.82%. From the whole of the contextual basic handout have a good quality and appropriate in use for teaching material of Biology in teaching learning process in SMK N 02 Batu. Â  Keywords: Contextual Basic Handout, Development and Quality of Handout. Â